Preparation method of battery diaphragm

By using the combination technology of PET and graphene composite layer, PI pore-generating layer, alumina lyophilic layer and PU silane adhesive layer in the battery separator, the lack of breathability and mechanical support of traditional separators in high-energy density batteries is solved. The problems of insufficient capabilities and insufficient interface bonding force have achieved higher mechanical strength, breathability and interface strength, improving the performance and safety of the battery.

CN119447691AInactive Publication Date: 2025-02-14SUZHOU SETH AIBO ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411517147.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional battery separators show insufficient breathability, insufficient mechanical support capacity and weak interface bonding in high-energy-density batteries, resulting in degradation of battery performance, accelerated aging and safety threats.

Method used

Polyethylene terephthalate (PET) is used to form a strength layer, and a mixture of polyimide (PI) and pore-generating agent is used to form a pore structure breathable layer, combined with chemical vapor deposition (CVD) or The sol-gel method coats alumina (Al2O3) to form a lyophilic layer, and uses polyurethane (PU) and silane coupling agent to form an adhesive layer. A three-layer composite separator is formed through lamination technology, and the surface is ionized. body treatment.

Benefits of technology

It significantly improves the mechanical support capacity, breathability and interface strength of the battery separator, ensures the stable operation of the battery under high-rate charging and discharging conditions, extends the service life of the battery, and improves the overall performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447691A_ABST
    Figure CN119447691A_ABST
Patent Text Reader

Abstract

According to the preparation method, PET and graphene are compounded to form a high-strength layer by utilizing a high-speed mixing and hot-pressing technology, so that the mechanical property and the deformation resistance of the diaphragm are effectively enhanced, and the safety and stability of a battery structure are ensured; pI and a pore-foaming agent are combined to prepare a breathable layer with an optimized pore structure, so that the breathability and the structural strength are balanced, and the operation efficiency and the safety of the battery under high-rate charge and discharge conditions are improved; the breathable layer is coated with aluminum oxide through a chemical vapor deposition or sol-gel method to form a lyophilic layer, and the interlayer bonding force is enhanced by combining PU and a silane coupling agent, so that the lyophilic property and the interface strength are improved, the permeation efficiency of an electrolyte is optimized, and the internal resistance of the battery is reduced; the surface of the diaphragm is modified through plasma treatment, so that the overall performance is further improved; the defects of a traditional battery diaphragm in the aspects of mechanical support, air permeability, lyophilic property and the like are overcome, and the overall performance of the battery is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery separators, and in particular to a method for preparing a battery separator. Background Art

[0002] With the rapid development of energy storage technology, lithium-ion batteries, as mainstream energy storage devices, have been widely used in electric vehicles, portable electronic devices, energy storage power stations, etc. However, with the continuous improvement of battery performance requirements, such as higher energy density, longer cycle life, faster charge and discharge speed, and higher safety, traditional battery separator technology has gradually exposed its limitations.

[0003] Traditional battery separators are mostly made of single polymer materials such as polyethylene (PE) and polypropylene (PP), which have a wide range of applications in the battery field. They do exhibit certain mechanical support capabilities and air permeability, and can meet the basic needs of general battery operation. However, with the rapid development of high-energy-density batteries, the performance bottlenecks of these traditional materials are becoming increasingly prominent.

[0004] First, during high-rate charge and discharge, the air permeability of traditional diaphragms is insufficient. Due to the relatively simple pore structure, it is unable to quickly adapt to the rapid penetration and exchange of electrolyte and gas, resulting in uneven distribution of electrolyte in the diaphragm, which in turn increases the internal resistance of the battery and reduces the charge and discharge efficiency. This not only limits the performance of the battery, but may also accelerate the aging process of the battery; on the other hand, the mechanical support capacity of the traditional diaphragm is also inadequate when facing the high pressure inside the battery and external impact. In high-energy density batteries, the internal pressure of the battery changes more dramatically, and traditional diaphragms are prone to deformation or even damage, which may not only cause the battery to short-circuit or fail, but also seriously threaten the safety of the battery; in addition, the interface bonding force between the traditional diaphragm and the electrode is also weak. In long-term charge and discharge cycles, this weak bonding force can easily lead to delamination or detachment between the diaphragm and the electrode, which in turn affects the stability and cycle life of the battery. This problem of interface strength further exacerbates the limitations of traditional diaphragms in high-performance battery applications.

[0005] Therefore, it is necessary to provide a method for preparing a battery separator to solve the above technical problems. Summary of the invention

[0006] The present invention overcomes the deficiencies of the prior art and provides a method for preparing a battery separator.

[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a battery separator, comprising the following steps:

[0008] S1: polyethylene terephthalate (PET) and graphene are mixed in a high-speed mixer, and then hot-pressed to form a strength layer with a thickness controlled at 50-100 μm;

[0009] S2: Dissolve PI in N-methylpyrrolidone (NMP), add porogen, fully stir and apply on the mechanical support layer, and then dry to form a porous structure breathable layer with a thickness controlled at 20-50 μm;

[0010] S3: preparing a lyophilic layer, coating an aluminum oxide (Al2O3) coating on the gas permeable layer using chemical vapor deposition (CVD) or a sol-gel method;

[0011] S4: forming a mixed adhesive mixture with polyurethane (PU) and silane coupling agent, and uniformly coating the adhesive mixture on the lyophilic layer for curing;

[0012] S5: stack all the layers together, use a laminator to laminate and then cure to form a three-layer composite diaphragm;

[0013] S6: Plasma treatment is performed on the surface of the three-layer composite diaphragm, and double-sided treatment is selected for the modified surface.

[0014] In a preferred embodiment of the present invention, in S1, the mass ratio of PET to graphene is 90:10-70:30, the mixing speed of the high-speed mixer is in the range of 2000-3000 rpm, the mixing time is in the range of 10-15 min, the hot pressing temperature is in the range of 180-220° C., and the hot pressing time is in the range of 5-10 min.

[0015] In a preferred embodiment of the present invention, in S2, the mass ratio of polyimide (PI) to the porogen is 95:5-85:15, the porogen is a mixture of DBP and Gly, the mass ratio of DBP to Gly is 90:30-70:10, the drying time is 10-20 min, and the drying temperature ranges from 80-120°C.

[0016] In a preferred embodiment of the present invention, in said S3, the processing condition of chemical vapor deposition (CVD) is that the CVD is processed at a temperature of 200-400° C. for 1-3 hours.

[0017] In a preferred embodiment of the present invention, in S3, the processing conditions of the sol-gel method are drying and curing at a temperature of 60-100° C. for 2-5 hours.

[0018] In a preferred embodiment of the present invention, in S4, the mass ratio of PU to silane coupling agent is 90:10 to 50:50, the curing temperature ranges from 60-100° C., and the curing time ranges from 1-2 h.

[0019] In a preferred embodiment of the present invention, in S5, the operating temperature range of the laminator is 100-200° C., the pressure range is 5-10 MPa, and the lamination time range is 5-10 min.

[0020] In a preferred embodiment of the present invention, in S5, the curing temperature ranges from 120 to 180° C., and the curing time ranges from 2 to 4 hours.

[0021] In a preferred embodiment of the present invention, in S6, the plasma treatment conditions are a power range of 50-200 W and a treatment time of 30-120 s.

[0022] In a preferred embodiment of the present invention, in said S6, the thickness of the modified layer is controlled to be 0.1-5 μm.

[0023] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0024] (1) The present invention provides a method for preparing a battery separator. First, polyethylene terephthalate (PET) and graphene are compounded by high-speed mixing and hot pressing technology to form a strength layer. The thickness of the layer is strictly controlled at 50-100 μm. The addition of graphene significantly enhances the mechanical properties of the PET substrate. Due to its excellent mechanical strength and excellent thermal stability, it can effectively improve the mechanical support capacity of the entire separator. This feature enables the battery separator of the present invention to exhibit higher deformation resistance and longer service life when subjected to internal pressure changes and external impacts of the battery, thereby ensuring the integrity and safety of the battery structure. Compared with traditional single-material separators, the mechanical support capacity is significantly improved through the composite material design, reducing the risk of battery failure due to material fatigue or damage, extending the service life of the battery, and enhancing the mechanical support capacity.

[0025] (2) In the preparation process, the present invention adopts a method of dissolving polyimide (PI) in N-methylpyrrolidone (NMP) and adding a porogen (a mixture of DBP and Gly) in a specific proportion. After coating and drying, a breathable layer with a controlled pore structure is formed, which ensures sufficient porosity and maintains good structural stability. The battery separator can effectively prevent direct contact between active substances while ensuring the permeation efficiency of gas and electrolyte, thereby improving the safety performance of the battery. Compared with the traditional separator with a single pore structure, the present invention achieves an optimal balance between permeability and structural strength by regulating the pore structure, solves the battery performance degradation caused by insufficient permeability and the safety problems that may be caused by excessive permeability, and the optimized permeability helps the battery to operate stably under high-rate charge and discharge conditions, thereby improving the overall performance of the battery and user experience.

[0026] (3) The present invention uses chemical vapor deposition (CVD) or sol-gel method to coat aluminum oxide (Al2O3) on the air permeability layer to form a lyophilic layer, and then mixes polyurethane (PU) with a silane coupling agent, applies the coating and solidifies it, forming a surface layer that is both lyophilic and has high interface strength; the aluminum oxide coating improves the lyophilicity of the diaphragm and promotes the uniform distribution of the electrolyte; and the combination of PU and silane coupling agent enhances the bonding force between the layers, and the improvement of lyophilicity ensures the rapid penetration and uniform distribution of the electrolyte in the diaphragm, reduces the internal resistance of the battery, and improves the charge and discharge efficiency. At the same time, the enhanced interface strength ensures the close combination of the layers during the battery charge and discharge cycle, avoiding stratification or shedding; compared with the diaphragm that simply relies on the inherent properties of the material to improve the lyophilicity and interface strength, the surface modification and composite material design achieve a dual improvement in lyophilicity and interface strength, significantly improving the overall performance and stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 It is a flow chart of a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0031] like Figure 1 As shown, the present invention provides a method for preparing a battery separator, comprising the following steps:

[0032] S1: polyethylene terephthalate (PET) and graphene are mixed in a high-speed mixer, and then hot-pressed to form a strength layer with a thickness controlled at 50-100 μm, the mass ratio of PET to graphene is 90:10-70:30, the mixing speed of the high-speed mixer is in the range of 2000-3000 rpm, the mixing time is in the range of 10-15 min, the hot-pressing temperature is in the range of 180-220° C., and the hot-pressing time is in the range of 5-10 min;

[0033] S2: dissolving PI in N-methylpyrrolidone (NMP), adding porogen, coating on the mechanical support layer after sufficient stirring, and then drying to form a porous structure breathable layer with a thickness controlled at 20-50 μm, the mass ratio of polyimide (PI) and porogen is 95:5-85:15, the porogen is a mixture of DBP and Gly, the mass ratio of DBP and Gly is 90:30-70:10, the drying time is 10-20 min, and the drying temperature range is 80-120 ° C;

[0034] S3: preparing a lyophilic layer, coating an aluminum oxide (Al2O3) coating on the air permeable layer by chemical vapor deposition (CVD) or sol-gel method, wherein the processing conditions of chemical vapor deposition (CVD) are CVD at a temperature of 200-400° C. for 1-3 h, and the processing conditions of sol-gel method are drying and curing at a temperature of 60-100° C. for 2-5 h;

[0035] S4: forming a mixed adhesive mixture with polyurethane (PU) and silane coupling agent, and uniformly coating the adhesive mixture on the lyophilic layer for curing, wherein the mass ratio of PU to silane coupling agent is 90:10 to 50:50, the curing temperature ranges from 60 to 100° C., and the curing time ranges from 1 to 2;

[0036] S5: stack all the layers together, use a laminator to laminate and then cure to form a three-layer composite diaphragm. The operating temperature range of the laminator is 100-200℃, the pressure range is 5-10MPa, the lamination time range is 5-10min, the curing temperature range is 120-180℃, and the curing time range is 2-4h;

[0037] S6: Plasma treatment is performed on the surface of the three-layer composite diaphragm, and the modified surface is double-sided treated. The plasma treatment conditions are as follows: the power range is 50-200W, the treatment time is 30-120s, and the thickness of the modified layer is controlled at 0.1-5μm.

[0038] It should be noted that: through steps S1-S6, a three-layer composite diaphragm with excellent performance was successfully constructed. First, in step S1, polyethylene terephthalate (PET) and graphene were uniformly mixed by a high-speed mixer and hot-pressed to form a strength layer, which not only ensured the uniform distribution of the material, but also achieved a balance between strength and conductivity by adjusting the material ratio and process parameters, providing a solid mechanical support for the diaphragm; then, in step S2, a mixture of polyimide (PI) and porogen was coated and dried on the mechanical support layer to form a porous structure breathable layer, and the pore size and distribution were controlled by adjusting the porogen ratio and drying conditions, thereby optimizing the breathability of the diaphragm; next, in step S3, an aluminum oxide (Al2O3) coating was applied to the breathable layer by chemical vapor deposition (CVD) or sol-gel method, which significantly improved The lyophilicity of the diaphragm contributes to the uniform distribution and infiltration of the electrolyte, thereby reducing the internal resistance of the battery. In step S4, a mixed adhesive of polyurethane (PU) and silane coupling agent is evenly coated on the lyophilic layer and cured, thereby enhancing the bonding force between the layers and improving the overall strength and stability of the diaphragm. Subsequently, step S5 stacks all the layers together for lamination and curing, thereby ensuring a close bond between the layers, thereby forming a three-layer composite diaphragm with high strength, good air permeability and lyophilicity. Finally, in step S6, the surface of the composite diaphragm is ion treated to further improve its surface properties, such as wettability and adhesion, and through double-sided treatment and control of the thickness of the modified layer, the performance of both sides of the diaphragm is balanced, thereby improving the performance and cycle stability of the battery.

[0039] Embodiment 1:

[0040] S1: Polyethylene terephthalate (PET) and graphene were selected as mixed materials. The mass ratio of PET to graphene was set to 80:20 to balance strength and conductivity. The materials were mixed in a high-speed mixer at a speed of 2500 rpm for 12 minutes. The mixed materials were kept at a hot pressing temperature of 200°C for 8 minutes to form a strength layer with a thickness of 75 μm.

[0041] S2: Select polyimide (PI) as the main material, and a mixture of DBP and Gly as the porogen, wherein the mass ratio of DBP to Gly is 80:20, dissolve PI in N-methylpyrrolidone (NMP), then add the porogen, stir thoroughly until a uniform solution is formed, apply the solution on the mechanical support layer, and then dry it at 100°C for 15 minutes to form a porous structure breathable layer with a thickness of 30 μm;

[0042] S3: coating an aluminum oxide (Al2O3) coating on the gas permeable layer by a chemical vapor deposition (CVD) method, and performing a CVD treatment at a temperature of 300° C. for 2 hours to form a uniform and dense aluminum oxide coating;

[0043] S4: polyurethane (PU) and silane coupling agent are mixed in a mass ratio of 60:40 to form an adhesive mixture, the adhesive mixture is evenly coated on the lyophilic layer, and then cured at a temperature of 80° C. for 1.5 hours to ensure that the adhesive is fully cured and forms a strong bonding interface;

[0044] S5: stack the strength layer, air permeable layer, lyophilic layer and adhesive layer prepared in S1, S2, S3 and S4 together, use a laminator to laminate for 7 minutes at 150°C and 8MPa, and then perform overall curing at 150°C for 3 hours to ensure that the layers are tightly bonded to form a three-layer composite diaphragm with high strength, good air permeability and lyophilicity;

[0045] S6: Plasma treatment is performed on both sides of the three-layer composite diaphragm, with a power of 150 W and a treatment time of 60 seconds. The thickness of the modified layer is controlled at about 2 μm.

[0046] Comparative Example 1:

[0047] S1: Polyethylene terephthalate (PET) and graphene. The mass ratio of PET to graphene is adjusted to 95:5. The mixture is mixed in a high-speed mixer at a speed of 2500 rpm for 12 minutes. The mixed material is kept at a hot pressing temperature of 200°C for 8 minutes to form a strength layer with a thickness of about 75 μm.

[0048] Subsequent steps S2-S6 are performed according to the parameters and methods of the first embodiment.

[0049] Comparative Example 2:

[0050] S2: The material is: a mixture of polyimide (PI), DBP and Gly as a porogen, the mass ratio of PI to the porogen is set to 90:10, and the mass ratio of DBP to Gly is adjusted to 50:50. PI is dissolved in N-methylpyrrolidone (NMP), and then the mixed porogen is added and stirred thoroughly until a uniform solution is formed. The above solution is coated on the mechanical support layer and then dried at 100°C for 15 minutes to form a porous structure breathable layer with a thickness of about 30 microns.

[0051] Step S1 and subsequent steps S3-S6 are performed according to the parameters and methods of Example 1.

[0052] Comparative Example 3:

[0053] S3: An aluminum oxide (Al2O3) coating is applied to the air permeable layer by a dip coating method instead of a chemical vapor deposition (CVD) method. The air permeable layer is immersed in an aluminum oxide solution, and then taken out and dried naturally or at a relatively low temperature to form an aluminum oxide coating.

[0054] Steps S1-S2 and subsequent steps S4-S6 are performed according to the parameters and methods of the first embodiment.

[0055] Comparative Example 4:

[0056] S4: The preparation of the adhesive layer is omitted. The coating and curing steps of the adhesive layer are completely omitted during the preparation process. There is no special adhesive layer to connect the layer structures (strength layer, breathable layer, liquid-philic layer).

[0057] Subsequent S5-S6 steps: Although the S4 step was omitted, for comparison purposes, the S5 step was still used for lamination and curing, and the S6 step was also used for plasma treatment.

[0058] Comparative Example 5:

[0059] S1: polyethylene terephthalate (PET) is selected as the material, and the material is kept at a hot pressing temperature of 200°C for 8 minutes to form a strength layer with a thickness of 75 μm;

[0060] S2: Select polyimide (PI) as the material, dissolve PI in N-methylpyrrolidone (NMP), coat the solution on the mechanical support layer, and dry it at 100°C for 15 minutes to form a porous structure breathable layer with a thickness of 30 μm;

[0061] S3: coating an aluminum oxide (Al2O3) coating on the gas permeable layer by a chemical vapor deposition (CVD) method, and performing a CVD treatment at a temperature of 300° C. for 2 hours to form a uniform and dense aluminum oxide coating;

[0062] S4: The strength layer, the air permeable layer, and the liquid-philic layer prepared by S1, S2, and S3 are stacked together, and laminated for 7 minutes at 150°C and 8MPa using a laminator, and then the whole is cured at 150°C for 3 hours to ensure that the layers are tightly bonded to form a three-layer composite membrane with high strength, good air permeability, and liquid-philicity;

[0063] S5: Plasma treatment is performed on both sides of the three-layer composite diaphragm, with a power of 150 W and a treatment time of 60 seconds. The thickness of the modified layer is controlled at about 2 μm.

[0064] Experiment 1:

[0065] Experimental purpose: To verify the advantages of Example 1 in terms of mechanical support capability, air permeability, lyophilicity and interface strength;

[0066] Experimental materials: prepared according to the materials and proportions in Example 1 and Comparative Examples 1 to 5;

[0067] Experimental procedures

[0068] Mechanical support capacity test: Use a tensile testing machine to perform a tensile test on each diaphragm, and record the breaking strength and elongation at break;

[0069] Air permeability test: Use an air permeability tester to measure the air permeability (Gurley value or specific gas permeability) of each diaphragm;

[0070] Lyophilicity test: The contact angle of the electrolyte (such as the electrolyte commonly used in lithium-ion batteries) on the surface of the diaphragm is measured by a contact angle meter to evaluate the lyophilicity;

[0071] Interface strength test: Use an interface strength tester to perform a peel test on the diaphragm to evaluate the bonding strength between the layers.

[0072] Table 1: Mechanical support capacity test

[0073] Embodiment 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Breaking strength(MPa) 120.56 90.34 115.23 110.01 85.67 105.45 Elongation at break (%) 5.23 3.89 4.98 4.56 3.12 4.21

[0074] Table 2: Air permeability test

[0075]

[0076]

[0077] Table 3: Air permeability test

[0078] Embodiment 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Contact angle (°) 15.23 20.45 18.98 22.12 - 17.65

[0079] Table 4: Interface strength test

[0080] Embodiment 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Peel strength (N / m) 25.67 18.90 22.34 19.87 12.01 20.56

[0081] It can be seen from Table 1 that the diaphragm of Example 1 has the highest breaking strength of 120.56MPa and a relatively high breaking elongation (5.23%), which indicates that it has excellent mechanical stability and toughness. Compared with other comparative examples, Example 1 maintains high strength while also showing good deformation ability, which is beneficial to resist changes in internal stress during battery charging and discharging, and ensure the safety and stability of the battery.

[0082] It can be seen from Table 2 that the Gurley value of Example 1 is the lowest at 230.45s / 100ml, indicating that it has the best air permeability. Good air permeability is one of the key properties of battery separators, which can ensure the rapid transmission of ions in the electrolyte, thereby improving the charging and discharging efficiency and performance of the battery. The excellent performance of Example 1 in this indicator further verifies its potential as a high-performance battery separator.

[0083] It can be seen from Table 3 that the contact angle of Example 1 is the smallest at 15.23°, indicating that it has the best wettability to the electrolyte, that is, the strongest lyophilicity. A diaphragm with good lyophilicity can contact the electrolyte more effectively, reduce the interface resistance, and improve the overall performance of the battery. The advantage of Example 1 in this aspect helps to improve the energy density and cycle life of the battery.

[0084] It can be seen from Table 4 that the peel strength of Example 1 is the highest at 25.67 N / m, which means that the bonding strength between its layers is the strongest. Interface strength is one of the important indicators for evaluating the stability of battery separators, which directly affects the durability and reliability of the separator in battery operation. Example 1 achieves a close bond between the layers through an optimized preparation process and a reasonable material ratio, thereby improving the overall performance and service life of the separator.

[0085] In summary:

[0086] Experiment 1 verified the significant advantages of Example 1 as a high-performance battery separator by evaluating the performance of Example 1 and Comparative Examples 1 to 5 in four key performance aspects: mechanical support capacity, air permeability, lyophilicity, and interface strength. Example 1 not only exhibits the highest breaking strength and relatively high elongation at break, ensuring excellent mechanical stability and toughness; at the same time, its lowest Gurley value indicates that it has the best air permeability, which is beneficial to improving the charging and discharging efficiency and performance of the battery. In addition, Example 1 also has the strongest lyophilicity, which enables more effective contact with the electrolyte, reduces interfacial resistance, and thus improves the overall performance of the battery. Finally, its highest peel strength proves the close bonding between the layers, enhancing the durability and reliability of the separator.

[0087] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a battery separator, characterized in that: The following steps are involved: S1: polyethylene terephthalate (PET) and graphene are mixed in a high-speed mixer, and then hot-pressed to form a strength layer with a thickness controlled at 50-100 μm; S2: Dissolve PI in N-methylpyrrolidone (NMP), add porogen, fully stir and apply on the mechanical support layer, and then dry to form a porous structure breathable layer with a thickness controlled at 20-50 μm; S3: preparing a lyophilic layer, coating an aluminum oxide (Al2O3) coating on the gas permeable layer using chemical vapor deposition (CVD) or a sol-gel method; S4: forming a mixed adhesive mixture with polyurethane (PU) and silane coupling agent, and uniformly coating the adhesive mixture on the lyophilic layer for curing; S5: stack all the layers together, use a laminator to laminate and then cure to form a three-layer composite diaphragm; S6: Plasma treatment is performed on the surface of the three-layer composite diaphragm, and double-sided treatment is selected for the modified surface.

2. The method for preparing a battery separator according to claim 1, characterized in that: In the S1, the mass ratio of PET to graphene is 90:10-70:30, the mixing speed of the high-speed mixer is in the range of 2000-3000 rpm, the mixing time is in the range of 10-15 min, the hot pressing temperature is in the range of 180-220° C., and the hot pressing time is in the range of 5-10 min.

3. The method for preparing a battery separator according to claim 1, characterized in that: In the S2, the mass ratio of polyimide (PI) to the porogen is 95:5-85:15, the porogen is a mixture of DBP and Gly, the mass ratio of DBP to Gly is 90:30-70:10, the drying time is 10-20 min, and the drying temperature ranges from 80-120°C.

4. The method for preparing a battery separator according to claim 1, characterized in that: In the S3, the processing condition of chemical vapor deposition (CVD) is that the CVD is processed at a temperature of 200-400° C. for 1-3 hours.

5. The method for preparing a battery separator according to claim 1, characterized in that: In S3, the processing conditions of the sol-gel method are drying and curing at a temperature of 60-100° C. for 2-5 hours.

6. The method for preparing a battery separator according to claim 1, characterized in that: In the S4, the mass ratio of PU to silane coupling agent is 90:10 to 50:50, the curing temperature ranges from 60 to 100° C., and the curing time ranges from 1 to 2 hours.

7. The method for preparing a battery separator according to claim 1, characterized in that: In S5, the laminator is used at a temperature range of 100-200°C, a pressure range of 5-10 MPa, and a lamination time range of 5-10 min.

8. The method for preparing a battery separator according to claim 1, characterized in that: In the S5, the curing temperature ranges from 120 to 180° C., and the curing time ranges from 2 to 4 hours.

9. The method for preparing a battery separator according to claim 1, characterized in that: In S6, the plasma treatment conditions are as follows: the power range is 50-200 W, and the treatment time is 30-120 s.

10. The method for preparing a battery separator according to claim 1, characterized in that: In the step S6, the thickness of the modified layer is controlled to be 0.1-5 μm.

Citation Information

Cited By

  • Heat-resistant diaphragm as well as preparation method and application thereof

    CN121769436A